Respostas

2013-11-12T20:10:25-02:00
Resolva as equaçoes do segundo grau:
a) x2-6x-16=0
x² -6x -16=0
Aplicando baskara
6+ou- raiz quadrada de 36+64
             2
6+ou - 10     x'= 8       x"= -2
       2
b) 6x2-x-5=0
6x² -x -5+0
1+ou- raiz quadrada de  1 +120
             12
1+ou - 11     x'= 1       x"= - 10   =  5     
  12                                  12        6
c)x(x-1)=11x-36
x² -x = 11x -36
x² - x -11x +36=0
x² -12x +36=o
12+ou- raiz quadrada de 144- 144
              2
12+ou -0     x'= +6     
       2